2021
DOI: 10.1186/s40163-021-00147-8
|View full text |Cite
|
Sign up to set email alerts
|

The U-shaped crime recovery during COVID-19: evidence from national crime rates in Mexico

Abstract: The existing empirical evidence suggests a reduction in aggregate crime as a consequence of the COVID-19 lockdown. However, what happens when lockdown measures are relaxed? This paper considers how the COVID-19 pandemic affects crime rates throughout Mexico when the stay-at-home orders end. We use national crime data from Mexico’s National Public Security System, which reports municipality-level rates on assault & battery, theft & property crime, fraud, drug crimes & extortion, and homicides. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
5
24
0
3
Order By: Relevance
“…Interestingly, while most forms of violent crime appeared to return to the same levels seen before the pandemic, drug trafficking not only bounced back to pre-COVID levels, but post-pandemic rates were well above those seen before the pandemic. Similar results were found in a study that analysed drug seizures over time in the United States (Palamar et al, 2021), and Langton et al (2021) observed a peak in drug crime in England and Wales in May 2020, though a similar increase in drug crime was not observed in other countries (Balmori de la Miyar et al, 2021). It is still unclear whether recorded drug trafficking increased as a result of growth in police activity, as drug trafficking could have become more visible with less people walking the streets, or whether this reflects actual changes in the supply and demand of drugs.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Interestingly, while most forms of violent crime appeared to return to the same levels seen before the pandemic, drug trafficking not only bounced back to pre-COVID levels, but post-pandemic rates were well above those seen before the pandemic. Similar results were found in a study that analysed drug seizures over time in the United States (Palamar et al, 2021), and Langton et al (2021) observed a peak in drug crime in England and Wales in May 2020, though a similar increase in drug crime was not observed in other countries (Balmori de la Miyar et al, 2021). It is still unclear whether recorded drug trafficking increased as a result of growth in police activity, as drug trafficking could have become more visible with less people walking the streets, or whether this reflects actual changes in the supply and demand of drugs.…”
Section: Discussionsupporting
confidence: 85%
“…Langton et al (2021) showed that, after the first COVID-19 lockdown in the UK, crime started to bounce back to pre-COVID levels. Similar results were found by Balmori de la Miyar et al (2021) using data recorded in Mexico. Nix and Richards (2021) observed that domestic violence calls for police services in the US returned to pre-COVID levels when lockdown restrictions were lifted.…”
Section: Rapid Social Changes and Crime: The Covid-19 Casesupporting
confidence: 90%
See 3 more Smart Citations